Neuroprotective Effects of Urolithins A and B against H2O2-induced toxicity in PC12 cells - Tencomnao, Tewin; Theerasri, Atsadang; Janpaijit, Sakawrat; Prasansuklab, Anchalee (Science Essence Journal, 2025)
Oxidative stress has been consistently implicated in a range of neurodegenerative diseases (NDDs). This detrimental condition is caused by exaggerated reactive oxygen species (ROS) generation which results in damage to neuronal cells. Urolithin A and B (UA and UB) are natural compounds derived from ellagitannins, which are abundant in pomegranate and other fruits. Herein, neuroprotective potential and underlying mechanisms of UA and UB against H2O2-induced oxidative injury of PC12 cells were investigated in this study. We found that pretreatment with UA and UB significantly rescued H2O2-induced toxicity in a dose-dependent manner, as demonstrated by increased cell viability and reduced ROS production. The pretreatment of PC12 cells with UA and UB could also modulate the expression of apoptotic-related proteins thereby inhibiting H2O2-induced apoptosis. Moreover, UA and UB activated the Nrf2 signaling and upregulated the expression of antioxidant genes including catalase, heme oxygenase-1 and superoxide dismutase 1 (SOD1). Consistently, the activity of SOD1 was increased after pretreatment of PC12 with UA and UB in the presence of H2O2. Overall, our study provides supporting evidence on the neuroprotective potential of UA and UB against oxidative stress-induced neuronal damage. Together, the findings suggest that both UA and UB could have potential health benefits for NDDs therapy and prevention.